The Image of a Human in the Mirror of Russian Phraseological Units and Folklore - Azimjonovna, Akramova Amirahon (International Journal on Integrated Education, 2023)
The article deals with the phraseological units of the Russian languages as lexical means of describing a person; a complex of folk ideas about a person is revealed; the universal and specific parameters of the figurativeness underlying metaphorical transfers are determined.